Flow structure at different stages of heat transfer deterioration with upward, mixed turbulent flow of supercritical CO2 heated in vertical straight tube. (25th November 2020) - Liu, Xinxin; Xu, Xiaoxiao; Liu, Chao; Zhang, Shijie; He, Jiacheng; Dang, Chaobin
Highlights: The buffer layer flow states at heat transfer deterioration stage were compared. The quantitative criteria in terms of heat transfer deterioration were analyzed. A new heat transfer coefficient correlation was developed. Abstract: The mixed turbulent heat transfer characteristics of supercritical CO2 heated in a straight tube of diameter d  = 4 mm are experimentally and numerically investigated at a pressure p  = 8 MPa, mass flux G  = 278 kg/(m 2 s), heat flux q  = 15–35 kW/m 2, and inlet Reynolds number R ein  ≥ 14000. To identify the key factor affecting the heat transfer deterioration (HTD), the flow structures at different conditions are comparatively analyzed. The results show that the HTD accompanying abrupt increase in the wall temperature is mainly caused by buoyancy force rather than thermal acceleration. The M-type velocity profiles are observed at the initial, stable, and recovery stages of the HTD. The location of the salient point of the M-type velocity plays a major role in the different regions of the HTD. Similar to the salient point of the M-shaped velocity, the location at which the local fluid temperature T b (r) is equal to the pseudo-critical temperature T pc can also be an effective criterion for predicting the onset of HTD. Both the salient point of the M-shaped velocity and the location of T b (r) =  T pc demonstrate that the flow structure at the buffer layer (y + = 5–30) is the dominant factor that influences the onset of HTD. An analysis of the thermal resistance in cross section also confirms that the buffer layer is the dominant region for the HTD. Based on the analysis of the flow states at the buffer layer, a new correlation model is developed for accurately predicting the heat transfer coefficient of supercritical CO2 under the HTD condition.